A case of severe generalized pustular psoriasis successfully treated with IL-17A monoclonal antibody and granulocyte removal therapy - Keiki Shimada; Daisuke Katagiri; Aika Kato; Naoto Nunose; Motohiko Sato; Yuri Katayama; Kanako Terakawa; Takahito Niikura; Emi Sakamoto; Yuki Yoshizaki; Minami Suzuki; Takashi Fukaya; et al. (Renal Replacement Therapy, 2022)
Abstract Background Generalized pustular psoriasis (GPP) usually presents with fever, generalized flushing, and multiple sterile pustules on the skin, which histopathologically form subcorneal pustules characterized by Kogoj spongiform pustules. Granulocyte/monocyte adsorption apheresis (GMA) was approved in Japan in 2012. The use of biologics for psoriasis treatment is increasing. Several case reports have evaluated the combination of GMA and cyclosporine (CyA) for GPP. However, very few English reports on combining biologics and GMA in treating GPP exist. Case presentation A 79-year-old man with a history of hypertension, diabetes mellitus, chronic kidney disease, and atrial fibrillation was admitted. He had been consulting a dermatologist for psoriasis vulgaris (PV) since the age of 44. The patient was diagnosed with severe GPP and treated with 300 mg secukinumab (SEC) on day 3. SEC is a fully human monoclonal IgG1 antibody that targets IL-17A. Five doses were administered. In addition, GMA was administered once a week, three times from day 4. After the first administration of GMA, the inflammatory response and skin condition improved markedly. The patient was discharged from the hospital on day 34. Conclusions The present study is the first English-written report on the combined administration of SEC and GMA both instituted since admission for severe GPP, with immediate patient response to treatment. Notably, IL-17A plays a vital role in the pathogenesis of GPP. GMA can eliminate activated leukocytes, and the early introduction of combined IL-17 monoclonal antibody and GMA may allow disease suppression in patients with severe GPP, thus avoiding progression to multiorgan failure. Further studies may verify the effects of IL-17 monoclonal antibodies and GMA on severe GPP.